The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1139/cjfas-2012-0327
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypoxia on the metabolism of Greenland halibut (Reinhardtius hippoglossoides)

Abstract: Greenland halibut (Reinhardtius hippoglossoides), especially juveniles, are frequently found in severely hypoxic areas (18%–25% saturation) of the St. Lawrence Estuary. We investigated the tolerance of this species to hypoxia and evaluated the consequences of low oxygen levels on metabolic capacity. At 5 °C, juveniles had a higher critical oxygen threshold than adults (15% versus 11% saturation), indicating that they were less tolerant to hypoxia. Severe hypoxia (19% saturation) did not affect the juveniles' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 75 publications
2
37
0
1
Order By: Relevance
“…Therefore, deep water renewal must occur often enough to prevent hypoxia. As hypoxia threshold definitions vary [ Hofmann et al ., ], here a midvalue of 20% dissolved oxygen (DO) saturation will be used, which is within the range that Greenland Halibut have been found elsewhere [ Dupont‐Prinet et al ., ]. For Cumberland Sound's bottom temperatures, 20% DO saturation corresponds to an oxygen concentration of roughly 3 mg L −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, deep water renewal must occur often enough to prevent hypoxia. As hypoxia threshold definitions vary [ Hofmann et al ., ], here a midvalue of 20% dissolved oxygen (DO) saturation will be used, which is within the range that Greenland Halibut have been found elsewhere [ Dupont‐Prinet et al ., ]. For Cumberland Sound's bottom temperatures, 20% DO saturation corresponds to an oxygen concentration of roughly 3 mg L −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Even though no oxygen measurements have been previously reported in Cumberland Sound, based on the existence of a bottom‐dwelling population of Greenland Halibut in the sound [ Peklova et al ., ], we can assume that the deepest regions are not hypoxic. However, oxygen levels may be low, as Greenland Halibut have been found in regions with 18−25% oxygen saturation and can survive down to 15% in laboratory studies [ Dupont‐Prinet et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in northwestern Greenland, whereas fish also moved to the inner section of the fjord, this occurred during the summer ice-free period, although fishing effort may have biased the observed distribution pattern (Boje 2002). While Greenland halibut and flatfish generally have a low aerobic scope when compared with pelagic fishes (Dupont-Prinet et al 2013) and are reported to occur in high abundances at low The left panels (a, c, and e) are environmental variables recorded in the southern region of Cumberland Sound, including bottom dissolved oxygen and percent ice cover data for the entire deep water southern region (see Appendix S2; both significant factors in the GLMM) and temperature readings from near the mouth of the Sound (SMOUTH, Fig. Boje et al (2014) reported Greenland halibut occupying colder waters during the winter months in the deep inner icefjord of Disko Bay, a similar trend observed in this and a previous study in Cumberland Sound (Peklova et al 2012).…”
Section: Telemetry To Understand the Ecology Of Deep-water Marine Spementioning
confidence: 99%
“…In the southern deep region, fish occupied waters with oxygen concentrations of ~3.6-3.7 mg/L, similar to the values recorded during peak fish occurrence in the northern region. While Greenland halibut and flatfish generally have a low aerobic scope when compared with pelagic fishes (Dupont-Prinet et al 2013) and are reported to occur in high abundances at low Fig. 7.…”
Section: Telemetry To Understand the Ecology Of Deep-water Marine Spementioning
confidence: 99%
“…Intertidal invertebrates may be more tolerant as they are adapted to fluctuating environmental conditions (Leiva et al , ). By contrast, Vaquer‐Sunyer & Duarte () found that crustaceans were the least tolerant to hypoxia of all organisms they tested and that some tolerant groups such as bivalves may benefit from hypoxia due to reduced predation and competition, in a similar way to R. hippoglossoides (Mejri et al , ; Dupont‐Prinet et al , 2013 b ). Although bivalves may be more tolerant, sessile organisms will be generally more vulnerable as they cannot usually move to localities with higher oxygen concentrations if they need to, unlike mobile species such as fin fishes.…”
Section: Physiological Effectsmentioning
confidence: 99%